Information technologies for martial arts training systems - Pavlenko, A. V.; Vakhnin, N. A.; Yakovlev, S. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze demand for martial artists` needs sensitive information technologies support in the martial arts training and competitive process.